Analysis of the Impact of Enterprise Risk Management Implementation on the Organizational Performance (Case Study of PT. Asuransi) - Herniyati Rezeki; Nur Aisyah F. Pulungan (Budapest International Research and Critics University, 2022)
Organizational performance is an important indicator, not only for companies, but also for investors. Organizational performance assessment can be done by measuring the performance, organizational performance measurement can be done using a method or approach (Felisia, 2011). The measure used in performance evaluation is something important that needs to be considered because it will affect employee attitudes, such as perceptions of fairness, trust in superiors, and job satisfaction (Lau and Sholihin, 2005). still relatively new. Only the banking sector has its own rules regarding risk management because this sector has more risks than other sectors. Meanwhile, for other sectors, the practice of risk management itself is still combined with the practice of Good Corporate Governance (GCG) so that it is not yet effective. Then only in 2012, the National Committee on Governance Policy (KNKG) issued a Governance-Based Risk Management Guideline which is separate from the GCG Guidelines. But this rule is only limited to ethical encouragement or only as a recommendation and does not have a legal bond that requires companies to follow these rules. Risk management or Enterprise Risk Management (ERM) is a strategy used to evaluate and manage all risks in the company. This approach to managing organizational risk is often referred to as risk management. In the midst of an economic situation full of uncertainty in business competition and the complexity of business risks that companies must face, a risk management system is one of the main tools to reduce and handle any risks that may arise (Beasley et al., 2006 ;).” Based on the results of the analysis, it was found that there is a positive impact of risk identification, risk assessment, and risk mitigation on organization performance partially and simultaneously.